Effect of running exercise with and without the use of equipment Kangoo Jumps, in postural control: a case study. - Oliveira, Rodrigo Franco de; Oliveira, Priscila Daniele de; Szezerbaty, Stheace Kelly Fernandes; Oliveira, Laís Campos de; Almeida, Juliana Serpeloni de; Gil, André Wilson de Oliveira; Assis, Vitor Hugo Antunes; Oliveira, Raphael Gonçalves de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: There is increasing interest from the general population, the search for the most suitable and safe exercise programs. Some equipment, such as Kangoo Jumps (KJ), allows performing exercises with less impact on the joints, and probably infer on postural control. Objective: To investigate the effect of exercise submaximal exercise running with and without the use of equipment KJ on postural control variables. Method: Participated in the study with an individual 20 years old, male, equivalent to 86kg of body weight. The test was to evaluate the postural balance using a force platform with bipedal before and after conventional and adapted from Cooper (using the KJ) test support. The equilibrium parameters were recorded: (A- COP in cm2) of displacement of the center of pressure; average swing speed of the COP (MVeloc in cm/s) in the anteroposterior planes (A/P) and medial-lateral (M/L). Results: The results showed that after using the equipment KJ, A-COP (-39.70%) MVeloc the A/P (-20.66%) and M/L (-20.48%) were best compared with the race without using KJ test. Conclusion: It is concluded that after running exercise on submaximal exercise with the use of equipment KJ had become favorable outcome for postural balance. One such reason would be because of its system of absorption and dissipation of impact, which allows a better activation of the proprioceptive system through increasing the speed of afferent estimate. The intervention of this study shows that the use of the KJ has significant equipment to maintain postural stability near control values benefits. However, further studies are needed, due to lack of evidence of the parameters of this equipment and the small number in our sample.